Oxidative Coupling of Naphthols to Ketones: An Approach to 1, 2‐Diketones. Issue 6 (9th February 2018) - Deb, Mohit L.; Saikia, B‐Shriya; Rastogi, Gaurav K.; Baruah, Pranjal K.
Abstract: 1, 2‐Diketones are highly useful building blocks for the synthesis of pharmaceuticals, natural products and heterocycles. A simple and efficient route to 1, 2‐diketones is developed here. The strategy involves coupling of naphthols to methyl ketones via oxidative C−H functionalization of methyl group of ketones. CuI (10 mol %) is used as catalyst and FeSO4 .7H2 O (10 mol %) as additive, both of which are environmentally benign and cheap. The reaction is carried out in DMSO solvent at 120 o C for 8–10 h. Little amount of 1, 1′‐bi‐2‐naphthol (BINOL) is also formed as side product. A tentative mechanism is proposed for the reaction which demonstrates a free‐radical pathway. Although Cu(I) is used as catalyst, however, the in situ generated Cu(II) behaves as the active catalytic species. Aerial oxygen acts as the oxygen source for the newly formed carbonyl functional group. Abstract : Green vitriol in action: Copper (I) catalyzed oxidative coupling of methyl ketones to naphthols giving 1, 2‐diketones is reported. Iron salt is necessary as an additive for this reaction. The reagents used in the reaction are very cheap, easily available and environmentally benign. Although Cu(I) is used as catalyst, however, the in situ generated Cu(II) behaves as the active catalytic species. A tentative mechanism is proposed based on our control experiments.